The Influence of Chatbot Anthropomorphism on Trust, Intention, and Engagement of Indonesian State-Owned Bank Customers: Investigation Using the DOI Theory - Bernardinus Joko Prakosta Santu Aji; Yolanda Masnita; Kurniawati Kurniawati (Politeknik Negeri Bandung, 2023)
Nowadays, artificial intelligence (AI) is growing rapidly, especially in Indonesia. Chatbot is one of the new forms of technology in AI that works like humans. Its great development is evidenced by the major adoption of chatbots in various industrial sectors, especially in the banking industry. This study intends to investigate the anthropomorphism of chatbots as one influencing factor of the trust, intention, and engagement of state-owned bank customers in Indonesia. The study employed the DOI theory since consumer behavior toward new technology is determined by his beliefs on that particular technology. The research used non-probability sampling with a total of 108 respondents who had or frequently used chatbots for their needs. The data was processed using the Partial Least Square method to analyze the measurement and structural model. The results show that all variables of chatbot anthropomorphism have a positive effect on trust, intention, and engagement of state-owned bank customers in Indonesia. This study provides insight for bank managers to continuously develop chatbots in order to get better quality and security so that customer trust, intention and engagement can increase.